Minimum cost trend free 16-run foldover designs - Gupta, Seema; Budhraja, Veena; Sharma, Shreya (Brazilian Journal of Biometrics, 2026)
This paper proposes new 16-run foldover designs aimed at minimizing the number of level changes. The method involves selecting n - p independent columns from the main effects and interaction effects of a 24 full factorial experiment while avoiding run duplication to construct a 2n-p fractional factorial design. The remaining p columns are then generated using these selected independent columns to maintain cost efficiency. The number of level changes and trend-free factors are computed for all possible fold-over plans for both standard and new designs. The performance of the new designs is compared to standard designs proposed by Li and Lin (2003), Cheng and Steinberg (1991) and Coster (1993) using the criteria of minimum level change, maximum trend-free factors and uniformity exhibiting improved performance and cost-effectiveness.